Foreword - Epure, Manuela (Journal of Economic Development, Environment and People, 2018)
Digital transformation, occurred in the past recent years, impacts many areas: from economics to society and reveal new opportunities, today when half of the world’s population is connected to the Internet but less than half trust that technology will make their lives better[1]. “Over half of the global population is connected to the internet and has growing access to the sum total of human knowledge at their fingertips. The internet will increasingly bring about ever more transformational changes for human civilization. However, some of these changes will also bring unpredictable costs. We are just now beginning to better understand this ‘Faustian bargain’ ” says Al Gore, co-founder and chairman of Generation Investment Management. [1] World Economic Forum – Our Shared Digital Future: Building an Inclusive, Trustworthy and Sustainable Digital Society, p.3